using geographical information system to model the spread of tuberculosis in the university of ibadan,Nigeria. (2010)
Nigeria currently ranks as the fourth highest burdened nation with tuberculosis (TB) globally; hence, new perspectives of addressing treatment and control of the diseases are needed. New technology, such as geographical information systems (GIS), may be useful in this process. we therefore sought to identify geographical areas where on-going TB transmission was occurring by linking GIS technology with diseases surveillance in a university community in Ibada , Nigeria. retrospective data of TB incidence between 2004 and 2007 from the health centre in the university were cartographically mapped to show current trends in the spread of the disease and its geographic dispersion among those infected using ArcGIS 9.2 software and global positioning system (GPS). a total of 71 cases were detected over the study period. the mean age for the affected population was 27.76+ 8.46(SD); fifty six (78.87%) PATIENTS BEING STUDENTS WHILE 15 (21.13%) WERE WORKERS. THE NEAREST NEIGHBOUR DISTANCE ANALYSIS INDICATED A CLUSTERED PATTERN OF LOCATIONS; WITH ZIP CODE 2-CHARACTERIZED BY OVERCROWDING AND LIMITED ROOM SPACE HAVING INCREASED likelihood of on-going transmission. this study therefore provides a preliminary synopsis of uses of GIS in tuberculosis control in Nigeria; hence the need to explore it on a a larger scale.